2011
DOI: 10.2807/ese.16.06.19786-en
|View full text |Cite
|
Sign up to set email alerts
|

First case of meningococcal meningitis due to Neisseria meningitidis serogroup Z' in Slovenia, December 2010

Abstract: We report here on the identification of the first meningococcal meningitis case in Slovenia caused by Neisseria meningitidis serogroup Z' in December 2010. The 19-year-old patient had not left the country during the incubation period. The patient was hospitalised and given the antibiotic treatment with cefotaxime very early in the course of the disease. The patient did not develop any complications during hospitalisation and was discharged on 5 January 2011.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This is the first case in Turkey in which invasive meningococcal infection was originated from N. meningitidis serogroup Z. N. meningitidis serogroup Z rarely causes invasive meningococcal disease. 9 Although it does not usually lead to serious illness, our patient had meningitis and sepsis, a nonspecific macular rash was observed, and her clinical condition improved rapidly after antibiotic treatment. Vaccination as early as possible and covering as many serogroups as possible is the most important step in preventing this disease, and our patient was diagnosed at a very early age with the nonvaccine meningococcal serogroup.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This is the first case in Turkey in which invasive meningococcal infection was originated from N. meningitidis serogroup Z. N. meningitidis serogroup Z rarely causes invasive meningococcal disease. 9 Although it does not usually lead to serious illness, our patient had meningitis and sepsis, a nonspecific macular rash was observed, and her clinical condition improved rapidly after antibiotic treatment. Vaccination as early as possible and covering as many serogroups as possible is the most important step in preventing this disease, and our patient was diagnosed at a very early age with the nonvaccine meningococcal serogroup.…”
Section: Discussionmentioning
confidence: 69%
“…8 In the literature, the incidence of serogroup Z–induced invasive meningococcal infections is rare. 9 In a multicenter study on nasopharyngeal carriages in Turkey, serogroup Z was not found. 10 In contrast, a study on meningococcal meningitis showed that N. meningitidis serogroup W was the most prevalent in Turkey during 2005–2012, 11 while serogroup B was prominent between 2015 and 2018.…”
Section: Discussionmentioning
confidence: 97%